Public Relations as Mechanism for Improving Community Policing in Port Harcourt City Local Government Area – Case Study of Rivers State Police Command - Ifeanyi C. Ehule (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study explored the role of Public Relations as a Mechanism for Improving Community Policing in Port Harcourt City Local Government Area, with a focus on the Rivers State Police Command. The main objective was to explore how public relations can strengthen police community relations through communication, trust, and engagement. Specifically, the study investigated the extent PR improves community policing, assessed community understanding of police services, examined compliance of police activities with the law, and identified challenges hindering effective relations. The study was anchored on Social Identity Theory and Community Oriented Policing Theory. The population consisted of residents from six communities Nkpolu Orowurukwo, Abuloma, Oro-Minike, Ogunabali, Orijie, and Rumuadaolu—projected at 900,254 persons, alongside officers of the Rivers State Police Command. Using Taro Yamane’s formula at 10% precision, a sample size of 100 households was determined. Random sampling guided questionnaire distribution to community members and police officers. Findings revealed that 73% of community respondents and 83% of police officers agreed that PR strategies such as awareness campaigns, dialogue forums, and outreach programs improve trust, reduce tension, and foster cooperation. However, gaps remain in officer training, responsiveness to community needs, and institutionalizing PR practice in policing. The study therefore recommends enhanced officer training in PR and communication, expansion of inclusive engagement programs, improved service delivery, strengthened accountability mechanisms, and adequate resource allocation to PR units. It concludes that effective integration of public relations into policing is indispensable for building accountability, reducing conflict, and fostering sustainable police–community partnerships.